Penguatan Tata Kelola Keagamaan yang Moderat: Sinkronisasi Rumah Ibadah, Sinergitas Antarlembaga, dan Ruang Publik dalam Pembangunan Nasional - Fakhrurraji, Ahmad (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper explains that Indonesia as a multicultural country faces serious challenges in moderate religious governance. Although the constitution guarantees freedom of religion, reality shows that conflicts and discrimination are still rampant, especially in the establishment of houses of worship for minority groups. Inequality in the implementation of regulations, weak capacity of local governments, and minimal synergy between institutions are the main causes. This study uses a qualitative-descriptive approach method with policy studies as the main design, analyzed through the theories of incrementalism, capacity building, advocacy coalition framework, and collaborative governance. Data were analyzed from policy documents, institutional reports, and academic publications. The results of the study show that the Joint Decree of the 2 Ministers No. 9 and 8 of 2006 is often a source of multiple interpretations that open up discriminatory space. In addition, the FKUB has not carried out its mediation function effectively due to lack of training and dominance of one religious group. The study recommends revising the Joint Decree into a Presidential Regulation to strengthen legal legitimacy, accompanied by systemic training for regional officials and the establishment of an interfaith dialogue forum as an effort to build inclusive governance. This policy is expected to strengthen social harmony, guarantee religious justice, and accelerate civilized national development. A gradual and collaborative approach is key to the success of religious governance reform in Indonesia.